2016
DOI: 10.1590/0103-6440201600428
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Application of the Phosphoric Acid on the Bond Strength of Lithium Disilicate

Abstract: The objective of this study was to evaluate the effect of passive or active phosphoric acid (PA) application after hydrofluoric acid (HA) treatment on the microshear bond strength of lithium disilicate. Thirty ceramic discs were made with IPS Emax 2 (10 mm thick and 10 mm diameter). The specimens were divided into 3 groups, A: 9.6% HA application; AF: 9.6% HA application + cleaning with 37% PA in passive mode and AFF: 9.6% HA application + cleaning with 37% PA in active mode. For the microshear test, four tygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(18 reference statements)
3
10
0
1
Order By: Relevance
“…Giraldo et al [33] observed that the active application of phosphoric acid after 9.6% HF acid increases the microshear BS values between the resin cement and LDC. In the study of Lise et al [34], HF acid etching showed higher microshear BS values than those observed in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Giraldo et al [33] observed that the active application of phosphoric acid after 9.6% HF acid increases the microshear BS values between the resin cement and LDC. In the study of Lise et al [34], HF acid etching showed higher microshear BS values than those observed in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Neste estudo, o menor diâmetro utilizado foi de 0,55 mm, em que observamos maior dificuldade na precisão do corte do tubo, na execução da metodologia, perdendo maior quantidade de corpos-de-prova, quando comparado ao diâmetro de 0,76 mm, por defeitos de posicionamento e de cimentação. Talvez as dificuldades na execução destes testes de microcisalhamento levem a comunidade científica a retornar para diâmetros maiores (GIRALDO et al, 2016;CEKIC-NAGAS et al, 2016).…”
Section: Resultadounclassified
“…[5][6][7] The esthetic appearance is the main reason why patients with color changes seek dental therapy. 4,14,[20][21][22][23][24][25] Treatment planning involves different factors such as severity and type of the alteration, whether or not malocclusion is present, age and socioeconomic situation of patients, and gingival health. 9,12,23 Therefore, it is extremely important for a multidisciplinary team to participate in the evaluation, diagnosis, and combination of surgical/restorative techniques to resolve the esthetic and functional changes, 9,10,13 particularly in more complex clinical cases such as the one presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…4,15,20 Newly developed pressable lithium disilicate-reinforced glass ceramics, such as the IPS emax Press™ system, has become the ceramic of choice for many dentists due to the satisfactory marginal fit and improved physical properties, such as higher biaxial and fracture strength and preservation of esthetic characteristics, which precisely indicate them for the fabrication of ceramic veneers. 4,24 This is an etchable ceramic composed of 70% of lithium disilicate crystals. Its composition includes two crystalline phases and one glass phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation